A Bioinspired in vitro Lung Model to Study Particokinetics of Nano-/Microparticles Under Cyclic Stretch and Air-Liquid Interface Conditions - Doryab, Ali; Taskin, Mehmet Berat; Stahlhut, Philipp; Schröppel, Andreas; Orak, Sezer; Voss, Carola; Ahluwalia, Arti; Rehberg, Markus; Hilgendorff, Anne; Stöger, Tobias; Groll, Jürgen; Schmid, Otmar (Frontiers in Bioengineering and Biotechnology, 2021)
Evolution has endowed the lung with exceptional design providing a large surface area for gas exchange area (ca. 100 m2) in a relatively small tissue volume (ca. 6 L). This is possible due to a complex tissue architecture that has resulted in one of the most challenging organs to be recreated in the lab. The need for realistic and robust in vitro lung models becomes even more evident as causal therapies, especially for chronic respiratory diseases, are lacking. Here, we describe the CIVIC (Cyclic In VItro Cell-stretch) “breathing” lung bioreactor for pulmonary epithelial cells at the air-liquid interface (ALI) experiencing cyclic stretch while monitoring stretch-related parameters (amplitude, frequency, and membrane elastic modulus) under real-time conditions. The previously described biomimetic copolymeric BETA membrane (5 µm thick, bioactive, porous, and elastic) was attempted to be improved for even more biomimetic permeability, elasticity (elastic modulus and stretchability), and bioactivity by changing its chemical composition. This biphasic membrane supports both the initial formation of a tight monolayer of pulmonary epithelial cells (A549 and 16HBE14o–) under submerged conditions and the subsequent cell-stretch experiments at the ALI without preconditioning of the membrane. The newly manufactured versions of the BETA membrane did not improve the characteristics of the previously determined optimum BETA membrane (9.35% PCL and 6.34% gelatin [w/v solvent]). Hence, the optimum BETA membrane was used to investigate quantitatively the role of physiologic cyclic mechanical stretch (10% linear stretch; 0.33 Hz: light exercise conditions) on size-dependent cellular uptake and transepithelial transport of nanoparticles (100 nm) and microparticles (1000 nm) for alveolar epithelial cells (A549) under ALI conditions. Our results show that physiologic stretch enhances cellular uptake of 100 nm nanoparticles across the epithelial cell barrier, but the barrier becomes permeable for both nano- and micron-sized particles (100 nm and 1000 nm). This suggests that currently used static in vitro assays may underestimate cellular uptake and transbarrier transport of nanoparticles in the lung.